1980
DOI: 10.1002/jrs.1250090509
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra and conformations of (chloromethyl)cyclopropane and epichlorohydrin

Abstract: The IR and Raman spectra (4000-50 cm-') of (ch1oromethyl)cyclopropane and epichlorohydrin have been recorded in all three physical states. It has been concluded from the spectroscopic data and from variable temperature studies that (chloromethy1)cyclopropane exists as an equilibrium mixture of gauche (95Oh) and cis (so/,) conformers in the liquid state, while only the gauche form persists in the solid phase. The enthalpy difference between these two rotamers was found to be 1.40f 0.10 kcal mol-'. Similarly, ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…The assignments of the CH 2 bending modes are consistent with those of the corresponding modes for the similar molecules. ,, Between 1500 and 1330 cm -1 we observe C-type bands at 1478 and 1436 cm -1 , an A-type band at 1346 cm -1 , and a very weak Q transition at 1316 cm -1 in the infrared spectrum of the gas. All of these bands are also observed as sharp lines in the Raman spectrum of the gas at 1477, 1439, 1349, and 1317 cm -1 and they have been assigned to the C 1 H bend (A‘), CH 2 deformation (A‘), C 4 H bend (A‘ ‘), and C 4 H bend (A‘), respectively.…”
Section: Vibrational Assignmentsupporting
confidence: 84%
See 1 more Smart Citation
“…The assignments of the CH 2 bending modes are consistent with those of the corresponding modes for the similar molecules. ,, Between 1500 and 1330 cm -1 we observe C-type bands at 1478 and 1436 cm -1 , an A-type band at 1346 cm -1 , and a very weak Q transition at 1316 cm -1 in the infrared spectrum of the gas. All of these bands are also observed as sharp lines in the Raman spectrum of the gas at 1477, 1439, 1349, and 1317 cm -1 and they have been assigned to the C 1 H bend (A‘), CH 2 deformation (A‘), C 4 H bend (A‘ ‘), and C 4 H bend (A‘), respectively.…”
Section: Vibrational Assignmentsupporting
confidence: 84%
“…Three-membered ring hydrocarbon molecules substituted with an asymmetric internal rotor, such as a halomethyl group, are of interest to structural chemists since there are two or three possible conformations depending on the three-membered ring. For the halomethylcyclopropane molecules at room temperature in the gas phase, there is a mixture of two equivalent gauche conformers and a cis form with the gauche rotamer the dominant conformer for the chloride and bromide. Apparently the relative abundance of the cis conformer increases with decreased size of the halogen atom. ,, However, from the initial microwave studies , of chloromethylcyclopropane it was proposed that only the gauche rotamer was present at ambient temperature. For fluoromethylcyclopropane the most stable conformer is predicted from ab initio calculations at the MP4(SDQ)/6-311G(d,p)(SDQ)/6-311G(d,p) level to be the gauche form (H atom over the three-membered ring) by 70 cm -1 (0.84 kJ/mol).…”
Section: Introductionmentioning
confidence: 99%
“…For the halomethylcyclopropanes, c-C 3 H 5 CH 2 X, where X = F, Cl, Br, and I, initially there was considerable controversy as to whether more than one conformer of chloromethylcyclopropane was present at room temperature [1][2][3]. However, later studies [4][5][6] conclusively showed that the predominant form was the gauche conformer and from variable temperature studies of the infrared spectra of xenon solutions [7] the enthalpy difference was determined to be 274 ± 21 cm À1 (3.28 ± 0.25 kJ mol À1 ) with only 12% of the cis form present at room temperature. With other X substituents such as cyano ACN [8,9], and ethynyl AC"CH [10,11] groups the percent of the gauche form present at ambient temperature dropped to 72% and 52%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Kalasinsky and Wurrey from the vibrational and Δ H studies have concluded that the relative abundances of the isomers of chloromethylcyclopropane are 95% gauche and 5% cis in the liquid phase at room temperature. Further studies on the corresponding bromide and iodide molecules indicate that as the halogen atom increases in size the amount of the cis conformer decreases. …”
Section: Introductionmentioning
confidence: 99%